Development and evaluation of a leaflet for concerned family members and friends: ‘It’s safe to talk about suicide’ - Owens, Christabel (Health Educ J, 2017)
OBJECTIVES: Significant others can play a key role in suicide prevention, but little attention has been given to the resources they may need in order to do so effectively. Based on previous qualitative research and working in partnership with suicide prevention charities, we developed a simple educational leaflet to help family members and friends recognise and respond to a possible suicidal crisis. We disseminated 15,000 copies through a wide range of community agencies within one English local authority. This paper describes the development, distribution and evaluation of the leaflet. The aim of the evaluation was to assess how the distribution strategy was working, whether the leaflet was regarded as useful and acceptable, how it was being used and whether there were any concerns about its content. DESIGN: Interview study. METHODS: We conducted two rounds of semi-structured telephone interviews with every agency on the distribution list and in-depth qualitative interviews with a purposefully selected sub-sample. RESULTS: The leaflet was seen as filling an important gap. It was eagerly embraced by staff in frontline agencies, who passed it on to clients, used it for their own personal/professional development and to support clients or colleagues, or used it as a teaching aid. No concerns were raised about its content. CONCLUSION: Findings reveal a deep-seated fear of talking about suicide among frontline staff. They were using the leaflet in ways we had not anticipated, demonstrating lateral thinking and a real commitment to suicide prevention in agencies that are not typically associated with it.